Reactive Sulfur Species Omics Analysis in the Brain Tissue of the 5xFAD Mouse Model of Alzheimer's Disease - Ayaka Kinno; Shingo Kasamatsu; Takaaki Akaike; Hideshi Ihara (MDPI AG, 2023)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder whereby oxidative stress augmentation results in mitochondrial dysfunction and cell death by apoptosis. Emerging evidence indicates that reactive sulfur species (RSS), such as glutathione hydropersulfide (GSSH), is endogenously produced, functions as potent antioxidants, and regulate redox signaling through the formation of protein polysulfides. However, the relationship between RSS and AD pathogenesis is not fully understood. In this study, we analyzed endogenous RSS production in the brain tissue of a familial AD model (5xFAD) mouse using multiple RSS-omics approaches. Memory impairment, increased amyloid plaques, and neuroinflammation have been confirmed in 5xFAD mice. Quantitative RSS omics analysis revealed that the total polysulfide content was significantly decreased in the brains of 5xFAD mice, whereas there was no significant difference in the levels of glutathione, GSSH, or hydrogen sulfide between wild-type and 5xFAD mice. In contrast, a significant decline in the protein polysulfide status was observed in the brains of 5xFAD mice, suggesting that RSS production and subsequent redox signaling might be altered during the onset and progression of AD. Our findings have important implications for understanding the significance of RSS in the development of preventive and therapeutic strategies for AD.